Petroleum geology : from mature basins to new frontiers, proceedings of the 7th Petroleum Geology Conference held at the Queen Elizabeth II Conference Centre, London, 30 March - 2 April 2009 - Vining, B. A.; Pickering, S. C.; Allen, Mark (Petroleum geology conference series ;, 2010)
"The seventh conference, entitled: 'Petroleum Geology: from Mature Basins to New Frontiers', while also staying true to its roots, was a truly international conference, with sessions encompassing many of the petroleum provinces of the world, that is: Europe; Russia, the Former Soviet Union (FSU) and the circum Arctic; North Africa and the Middle East; and Passive Margins worldwide. As the world seeks new energy sources, it was most appropriate to have a session dedicated entirely to unconventional hydrocarbon resources. Regular features such as a core workshop were present. In addition, innovative new features, such as the geocontroversies debates and virtual field trips, both of which are described below, enhanced what was already a well established conference format."--Preface.